2012
DOI: 10.1177/1468087412455748
|View full text |Cite
|
Sign up to set email alerts
|

A practical guide for using proper orthogonal decomposition in engine research

Abstract: Proper orthogonal decomposition has been utilized for well over a decade to study turbulence and cyclic variation of flow and combustion properties in internal combustion engines. In addition, proper orthogonal decomposition is useful to quantitatively compare multi-cycle in-cylinder measurements with numerical simulations (large-eddy simulations). However, the application can be daunting, and physical interpretation of proper orthogonal decomposition can be ambiguous. In this paper, the mathematical procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 27 publications
0
73
0
Order By: Relevance
“…Thus, as in previous work [7,8], the mass-specific kinetic energy contribution of mode 1 in each snapshot is a good measure of its RANS ensemble average content, and the mass-specific kinetic energy contribution of modes 2 through M in each snapshot is a good measure of its the RANS turbulence content. The mass-specific kinetic energy contribution of a particular mode m to a snapshot k (ke m,k ) is calculated from the POD coefficient c k m as follows:…”
Section: P Abraham Et Al / Evaluating Large-eddy Simulation (Les) Amentioning
confidence: 78%
See 2 more Smart Citations
“…Thus, as in previous work [7,8], the mass-specific kinetic energy contribution of mode 1 in each snapshot is a good measure of its RANS ensemble average content, and the mass-specific kinetic energy contribution of modes 2 through M in each snapshot is a good measure of its the RANS turbulence content. The mass-specific kinetic energy contribution of a particular mode m to a snapshot k (ke m,k ) is calculated from the POD coefficient c k m as follows:…”
Section: P Abraham Et Al / Evaluating Large-eddy Simulation (Les) Amentioning
confidence: 78%
“…To demonstrate the attributes of this technique, phase-dependent POD was used to analyze snapshots at 76°ATDCE from 60 consecutive cycles from PIV and LES, respectively. Previous studies [7,8] have shown that the first mode Measured and computed ensemble-average (every second vector shown) and RMS velocity distributions.…”
Section: Phase-dependent Pod: Separate Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we focus on the snapshot POD method [6,7,24]. A detailed description of the underlying theory and the application for experimental and simulation data can be found in [21,24,25].…”
Section: Proper Orthogonal Decompositionmentioning
confidence: 99%
“…Furthermore, the remaining fluctuations are expected not to be associated with a variation of a coherent motion but rather being smaller scale turbulent fluctuations. To achieve this, our method combines POD, which has been used previously for the identification and investigation of velocity field fluctuations based both on experimental and numerical data [3][4][5][6][7][8][9], and conditional averaging [10].…”
Section: Introductionmentioning
confidence: 99%